A Multilevel Analysis of Child Care and the Transition to Motherhood in Western Germany - Karsten Hank; Michaela Kreyenfeld (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
In this paper, we take a multilevel perspective to investigate the role of child care in the transition to motherhood in Germany. We argue that in the European institutional context the availability of public day care and informal child care arrangements should be a central element of the local opportunity structure regarding the compatibility of childrearing and women's employment. Using data from the German Socio-Economic Panel, we apply a multilevel discrete time logit model to estimate first birth risks of western German women. While we find that access to informal care arrangements increases the probability of entering parenthood, we do not find any statistically significant effect of the public day care provision. This result probably points to shortcomings in the specific institutional set-up of the German day-care regime, and to the existence of potentially relevant unobserved dimensions of child care.
Keywords: 330; child care; fertility; multilevel analysis; Germany; Kinderbetreuung; Fruchtbarkeit; Frauenerwerbstätigkeit; Mütter; Schätzung; Deutschland